A cross-scale study on the relationship between urban expansion and ecosystem services in China. (1st October 2022) - Tian, Shiqi; Wu, Wei; Shen, Zhou; Wang, Jiao; Liu, Xueqing; Li, Linjuan; Li, Xiangcheng; Liu, Xiansheng; Chen, Hongshan
Abstract: Clarifying the relationship between urban expansion and ecosystem services (ESs) is critical for sustainable management of land resources and ecosystems. However, little is known about the relationship between the two at the cross-scale (particularly at the national-provincial scale). Therefore, we conducted a systematic assessment of the spatiotemporal dynamics and the relationship between urban expansion and ESs including food production (FP), soil conservation (SC), carbon sequestration (CS), and water yield (WY) in China from 1992 to 2020 on the national-provincial scale. The results show that China's urban expansion took up a large amount of cropland, accounting for 79.35% of the newly-added built-up land. Shandong had the largest expansion scale and the highest speed, Shanghai had the most pronounced expansion intensity, and more than 50% of the provinces were dominated by outlying expansion pattern. In terms of total change, the three ESs of FP, SC, and WY increased by 286.5 × 10 6  t, 1893.61 × 10 6  t, and 8337.20 × 10 6  mm, respectively, and CS decreased by 683.90 × 10 6  Mg C. However, in the urban expansion area, FP and CS net decreased by 1757.6 × 10 4  t and 19, 640.19 × 10 4  Mg C, respectively, while SC and WY net increased by 347.52 × 10 4  t and 20, 264.11 × 10 4  mm, respectively. Shandong contributed the most to changes in ESs in urban expansion areas. Urban expansion was significantly negatively correlated with FP and CS with the correlation coefficients > -0.8; it was significantly positively correlated with SC and WY, with coefficients of 0.714 and 0.413, respectively, and urban expansion had a lagged effect on ESs. The impact of urban expansion on ESs had a spatial spillover effect and showed prominent spatial clustering in Anhui, Henan, and Shandong. Based on these results, we proposed urban planning countermeasures grounded in the perspective of ES improvement, which would provide policy references for the sustainable management of the ecological environment and land resources. Highlights: Urban expansion and ESs at the national-provincial scale were quantified. The relationship between urban expansion and ESs varied by type of ESs. Shandong was the largest contributor to ESs changes in urban expansion areas. There were time lags and spatial spillovers between urban expansion and ESs.